Do cognitive heuristics underpin symptom appraisal for symptoms of cancer?: A secondary qualitative analysis across seven cancers. Issue 5 (18th March 2019) - Kummer, Sonja; Walter, Fiona M.; Chilcot, Joseph; Emery, Jon; Sutton, Stephen; Scott, Suzanne E.
Abstract: Objectives: To explore the evidence for cognitive heuristics or "rules of thumb" used within patients' reports of symptom appraisal and decisions to seek help for symptoms of cancer. Methods: A secondary analysis of interviews from existing studies that explored symptom appraisal in patients who had sought help for potential symptoms of cancer. Transcripts from n = 50 in‐depth interviews with patients referred with symptoms suspicious of cancer (pancreas, colorectal, oral, lung, melanoma, breast, and prostate) were re‐analysed using a deductive thematic approach underpinned by the heuristics outlined in the Common Sense Model of Illness Self‐regulation as set within the Model of Pathways to Treatment. Results: The most dominant heuristic in patient reports was the Rate of change rule (ie, symptoms that are worsening, increasing, or have a sudden onset [rather than improving, stable or decreasing in number] are more likely to indicate illness). There was also support for the Duration rule, Pattern rule, Chronology rule, Severity (of interference) rule, Age‐illness rule, Novelty rule, Similarity rule, Location rule, and Optimistic bias rule . There was a lack of evidence for the Prevalence and Stress‐illness rules . Conclusions: People do appear to use heuristics to guide their appraisal of symptoms and their perceived need for healthcare. Heuristics may be an important aspect underlying symptom misinterpretation, thus making them key targets for interventions. For instance, campaigns could tackle cognitive biases rather than focusing on specific symptom awareness. Myth‐busting messages could highlight that intermittent, mild symptoms, and symptoms that are not worsening can be signs of a serious health problem.